2022
DOI: 10.1542/peds.2020-045948e
|View full text |Cite
|
Sign up to set email alerts
|

All Quality Improvement Is Health Equity Work: Designing Improvement to Reduce Disparities

Abstract: Quality improvement (QI) can be a critical means by which to achieve equity in health and health care. QI efforts, however, often fail to be designed and implemented through the lens of health equity. In this article, we will discuss the current state of the intersection between QI and health equity, then lay out specific steps researchers and practitioners can take to ensure that their QI work reduces, rather than increases or maintains, existing disparities. These steps include first, understanding existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…A growing literature describes how structural and interpersonal racism can drive differences in how patients receive healthcare,34–37 countering the position that race and ethnicity are only a proxy for other factors. At the same time, more action-oriented frameworks have begun to demonstrate that improvement work focused on disparities can be effective in eliminating or countering the impact of these factors 38–40. The safety outcomes in our study (CLABSI and UE) have been shown to be sensitive to various technical and behavioural variables, including level of sedation and nursing care of the central line.…”
Section: Discussionmentioning
confidence: 73%
“…A growing literature describes how structural and interpersonal racism can drive differences in how patients receive healthcare,34–37 countering the position that race and ethnicity are only a proxy for other factors. At the same time, more action-oriented frameworks have begun to demonstrate that improvement work focused on disparities can be effective in eliminating or countering the impact of these factors 38–40. The safety outcomes in our study (CLABSI and UE) have been shown to be sensitive to various technical and behavioural variables, including level of sedation and nursing care of the central line.…”
Section: Discussionmentioning
confidence: 73%
“…To conduct quality improvement work that improves equity, teams should stratify outcomes to assess and understand disparities before starting quality improvement interventions . Quality improvement strategies to address disparities due to bias and racism require long-term organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to understand and address the drivers of care variation, but in the meantime, clinical groups can invest in monitoring quality metrics stratified by race, ethnicity, and language and engaging in equity-focused quality improvement efforts to address disparities identified locally. 58,59 Second, the new American Academy of Pediatrics guidelines take an important step in advocating for a patient-centered approach, highlighting opportunities for shared decisionmaking. Paradoxically, this could exacerbate disparities if there is bias in when and how clinicians engage in shared decisionmaking.…”
Section: Figure Inclusion and Exclusion Flow Diagrammentioning
confidence: 99%